2009
DOI: 10.1177/0961203309106763
|View full text |Cite
|
Sign up to set email alerts
|

Antithyroid antibodies in antiphospholipid syndrome: prevalence and clinical associations

Abstract: Autoimmune thyroid disease has been associated with several systemic autoimmune disorders. However, limited data are available regarding the prevalence and clinical associations of thyroid autoimmunity in antiphospholipid syndrome (APS). Seventy-five patients with APS, 75 patients with systemic lupus erythematosus (SLE) and 75 healthy controls were tested for the presence of antithyroid antibodies (ATAs) (anti-thyroglobulin and anti-thyroid peroxidase [anti-TPO]) using commercial ELISA. Clinical data were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Antibodies to thyroid microsomal [2] and myeloperoxidase (MPO) are associated with graves’ disease and thyroiditis [3], antinuclear antibodies (ANA) and rheumatoid factor(RF) represent a serology hallmark in the diagnosis of systemic autoimmune rheumatic disease (SARD) such as systemic lupus erythematosus [4]. Zona pellucida antibodies are associated with POI, antibodies to double-stranded DNA (ds-DNA), histone, nuclear ribonucleoprotein (RNP) and Smith antigen [5] are associated with SLE, whereas antibodies to Sjogren’s syndrome A (SSA/Ro) and Sjogren’s syndrome B(SSB/La) can occur in both SLE and Sjogren’s syndrome (SS).…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies to thyroid microsomal [2] and myeloperoxidase (MPO) are associated with graves’ disease and thyroiditis [3], antinuclear antibodies (ANA) and rheumatoid factor(RF) represent a serology hallmark in the diagnosis of systemic autoimmune rheumatic disease (SARD) such as systemic lupus erythematosus [4]. Zona pellucida antibodies are associated with POI, antibodies to double-stranded DNA (ds-DNA), histone, nuclear ribonucleoprotein (RNP) and Smith antigen [5] are associated with SLE, whereas antibodies to Sjogren’s syndrome A (SSA/Ro) and Sjogren’s syndrome B(SSB/La) can occur in both SLE and Sjogren’s syndrome (SS).…”
Section: Introductionmentioning
confidence: 99%
“…Results from the study by Mavragani et al showed that patients with APS (primary and secondary) are associated with antithyroid antibodies. 31 To date, our study is the first to report an association between APS and SLE patients with ATD. Further research on the underlying pathogenetic mechanisms is warranted, to allow better understanding in these autoimmune diseases.…”
Section: Discussionmentioning
confidence: 89%
“…Many of these series did not find any increase of antiphospholipid antibodies and antithyroid antibodies versus comparison groups [87][88][89]. One study found antithyroid antibodies in 27% of APS patients [90].…”
Section: Thyroid Involvement In Apsmentioning
confidence: 96%
“…Patients can have both antithyroid and antiphospholipid antibodies [77][78][79][80], including women with autoimmune thyroid disease [81][82][83][84][85][86][87][88][89]. Many of these series did not find any increase of antiphospholipid antibodies and antithyroid antibodies versus comparison groups [87][88][89].…”
Section: Thyroid Involvement In Apsmentioning
confidence: 98%